2018
DOI: 10.22555/joeed.v5i1.1421
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Management Practices in Public and Private Universities in Khyber Pakhtunkhwa

Abstract: <p> <em>This study attempted to compare the management practices in public and private universities in Khyber Pakhtunkhawa, Pakistan. The comparison is based on availability of written rules and regulations, distribution of tasks, availability of managers, access to officers, time management, work load, staff promotion procedure and appraisal system. Additionally, the comparison is also based on transparency, political intervention, use of authorities, nepotism and biasness, human resource availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
2
6
0
1
Order By: Relevance
“…Findings of the present study are similar to a study conducted in Islamabad which revealed that the practices of hospital wastes are better in private hospital than the public one [44]. Similarly, in other study conducted by Khan, Ihsan [39] in four tertiary care hospitals of Peshawar, i.e. two hospitals from public and two from private sectors revealed that private hospitals performed well practices for waste management as compared to public hospitals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Findings of the present study are similar to a study conducted in Islamabad which revealed that the practices of hospital wastes are better in private hospital than the public one [44]. Similarly, in other study conducted by Khan, Ihsan [39] in four tertiary care hospitals of Peshawar, i.e. two hospitals from public and two from private sectors revealed that private hospitals performed well practices for waste management as compared to public hospitals.…”
Section: Discussionsupporting
confidence: 88%
“…Comparing the present results with other studies around the world, as well as some studies conducted in major cities of Pakistan, clearly indicates that there was no proper, systematic management of hospital waste practiced [23,28,[36][37][38][39][40][41]. Although, (87.5%) surveyed hospitals have HWM plan and team with speci ed responsibilities.…”
Section: Discussionsupporting
confidence: 45%
“…The quantitative methodology was employed for collecting and interpreting data to generate results. This study has focused on the private HEIs because there are significant differences in the HRM practices and management between public and private HEIs (Khan, Aajiz & Ali, 2018). The data was collected from four regions/provinces of Pakistan including Khyber Pakhtunkhwa, Punjab, Sindh and Islamabad Capital Territory, the study excluded Azad Jammu and Kashmir and Balochistan as there was only one private HEI in these respective regions/provinces which means that there were no available choices for the faculty members of these HEIs to compare.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the public and private sector organizations' distinct governance systems, structures, and procedures, their employees are likely to have different job expectations, attitudes, feelings, and overall working behavior. Previous researchers have explored the differences in these work environment facets in various types of universities and colleges and their influence on the well-being of teachers (Singh, 2014;Mkumbo, 2014;Singh and Jain, 2015;Kang and Sidhu, 2015;Ahmad et al, 2015;Kaur and Sharma, 2016;Ansah-Hughes et al, 2017;Zábrodská et al, 2018;Khan et al, 2018;Dinc, 2018;Faisal et al, 2019;Dinibutun et al, 2020;Garg and Garg, 2020). Studies have found significant differences in the occupational stress level of teachers in public and private sector universities (Mkumbo, 2014;Faisal et al, 2019;Garg and Garg, 2020).…”
Section: Workload Social Status and Recognition Of The Teachersmentioning
confidence: 99%